1980
DOI: 10.1111/j.1365-2923.1980.tb02388.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the clinical problem-solving process using a simulation technique

Abstract: Currently, research does not agree as to the extent to which medical content and problem-solving processes underlie clinical problem-solving. The results of research in this area fall into two categories: (1) clinical problem-solving is primarily dependent upon medical content specific within the case, and (2) clinical problem-solving is a skill, or series of skills, which can be applied to all clinical problems. In the study reported in this paper, seventy-one second-year medical students who had completed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…The results of a factor analysis of a single set of data cannot be definitive, although at least one other study (Harasym et al , 1980) has produced somewhat comparable conclusions. Confirmation of our results could have important implications for our understanding of the nature of clinical competence and its measurement.…”
Section: Discussionmentioning
confidence: 98%
“…The results of a factor analysis of a single set of data cannot be definitive, although at least one other study (Harasym et al , 1980) has produced somewhat comparable conclusions. Confirmation of our results could have important implications for our understanding of the nature of clinical competence and its measurement.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, a diversity of clinical experiences could have led to higher scores on the NBME Special Examination in Medicine, but not necessarily on the locally developed examinations. Indeed, Harasym et al (1980) found that some clinical problem‐solving skills, such as history‐taking and hypothesis generation, are acquired general skills which are transferrable from one patient problem to another. By extension of Harasym's findings, these skills may also be transferrable from one specialty to another.…”
Section: Discussionmentioning
confidence: 99%
“…Harasym et al (1980) evaluated the clinical problem‐solving process and as a result of this study concluded that data gathering and hypothesis generation are specific problem‐solving skills while hypothesis refinement, physical examination, laboratory investigations and diagnosis are case dependent. The model used in this study appears to be similar to the modified essay question (MEQ) rather than to the PMP.…”
Section: Some Outcomes Of Recent Researchmentioning
confidence: 99%